Preparation method of modified lithium-rich manganese-based positive electrode material and positive electrode material

By wet-covering the precursor and mixing it with the lithium source, the shortcomings of the existing lithium-rich manganese-based positive electrode materials in terms of cycle performance and rate performance are solved, the process steps are simplified and the material performance is improved, and it is suitable for industrial production.

CN119920871APending Publication Date: 2025-05-02NINGBO FULI BATTERY MATERIAL TECH CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411878299.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

The existing lithium-rich manganese-based positive electrode materials have shortcomings in terms of cycle performance and rate performance, and common modification methods such as doping and coating have problems such as complex process, high energy consumption and high production costs.

Method used

A method of preparing a modified lithium-rich manganese-based positive electrode material is adopted to coat the precursor by wet method and mixed with the lithium source to achieve simultaneous generation of the cladding layer and the inner layer, simplifying the process steps and improving the material performance.

Benefits of technology

This method improves the discharge specific capacity and rate performance of the positive electrode material, simplifies the process flow, reduces production costs, is suitable for industrial production, and helps design high-safe, high specific energy, and long-life lithium-ion batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119920871A_ABST
    Figure CN119920871A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a modified lithium-rich manganese-based positive electrode material and the positive electrode material. The preparation method comprises the following steps: (1) respectively preparing aqueous solutions of nickel-cobalt-manganese metal ions, a precipitator and a complexing agent; (2) adding the nickel-cobalt-manganese metal ion solution, the precipitant solution and the complexing agent solution into a reaction kettle for reaction to obtain a suspension; (3) washing, filtering and drying the suspension to obtain a nickel-cobalt-manganese composite material precursor; the chemical formula of the nickel-cobalt-manganese composite material precursor is Mn < x > Ni < y > Co < z > (OH) < 2 > or Mn < x > Ni < y > Co < z > CO < 3 >, 1, 0.1 lt; yt; Yt; 0, 0.5, 0 lt; zlt, zlt; 0.3 part; (4) adding the nickel-cobalt-manganese composite material precursor Mn < x > Ni < y > Co < z > (OH) < 2 > or Mn < x > Ni < y > Co < z > CO < 3 >, a titanium source, an aluminum source and a phosphate radical source into an organic solvent for mixing, heating, stirring and mixing at 40-80 DEG C, and drying at 80-120 DEG C to obtain an aluminum-titanium phosphate coated precursor; and (5) grinding the aluminum titanium phosphate coated precursor, mixing with a lithium source, and sintering at 400-950 DEG C to obtain the positive electrode material. The scheme of the invention has the advantages of being higher in capacity, better in cycle performance, simple and easy to implement, and capable of realizing industrialization.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of positive electrode material preparation, and specifically to a preparation method of a modified lithium-rich manganese-based positive electrode material and the positive electrode material. Background Art

[0002] Lithium-ion battery is a new type of high-energy battery invented in the 20th century. With the development of society, people have higher and higher requirements for energy storage and new energy power batteries, and are pursuing higher specific capacity and safer lithium-ion batteries.

[0003] Lithium-rich manganese-based positive electrode materials have attracted widespread attention from the academic community for their high specific capacity (>250mAh / g), low cost and high voltage. However, their low first-cycle coulombic efficiency, poor rate performance, and rapid capacity and voltage decay have hindered their application and development. Currently, the common modification methods are doping and coating, but the doping modification method generally sacrifices the specific capacity, and the coating modification method requires adding a secondary sintering on the basis of the primary sintering, which is complex in process, increases energy consumption, and increases production costs. Summary of the invention

[0004] In view of the above-mentioned deficiencies in the prior art, the present application provides a coating method for preparing a lithium-rich manganese-based positive electrode material with higher capacity and better cycle performance, which is simple and easy to implement industrially.

[0005] In order to solve the above technical problems, the technical solution adopted in this application is: a method for preparing a modified lithium-rich manganese-based positive electrode material, the steps of the method comprising:

[0006] (1) First, prepare a nickel-cobalt-manganese metal ion solution, a precipitant solution, and a complexing agent solution, respectively, wherein the nickel-cobalt-manganese metal ion solution, the precipitant solution, and the complexing agent solution are all aqueous solutions;

[0007] (2) adding a nickel, cobalt and manganese metal ion solution, a precipitant solution and a complexing agent solution into a reaction kettle through a metering pump to react and obtain a suspension;

[0008] (3) washing, filtering and drying the suspension to obtain a nickel-cobalt-manganese composite material precursor; the chemical formula of the nickel-cobalt-manganese composite material precursor is Mn x Ni y Co z (OH) 2 or Mn x Ni y Co z CO 3 , where 0.5≤x<1, 0.1 <y<0.5,0<z<0.3;

[0009] (4) The nickel-cobalt-manganese composite material precursor Mn xNi y Co z (OH) 2 or Mn x Ni y Co z CO 3 , titanium source, aluminum source, and phosphate source are added to an organic solvent and mixed, heated and stirred at 40-80° C., and then dried at 80-120° C. to obtain an aluminum-titanium phosphate-coated precursor;

[0010] (5) The aluminum-titanium phosphate-coated precursor is ground and mixed with a lithium source, and sintered at 400-950° C. to obtain a fast ion conductor-coated lithium-rich manganese-based positive electrode material.

[0011] Furthermore, the concentration of the nickel, cobalt and manganese metal ion solution in step (1) is 0.5-3 mol / L (total concentration of the three elements nickel, cobalt and manganese).

[0012] Furthermore, the molar ratio of nickel salt, cobalt salt and manganese salt in the nickel-cobalt-manganese metal ion solution in step (1) is (1-35):(0.8-5):(4-65).

[0013] Furthermore, the concentration of the precipitant solution in step (1) is 1-3 mol / L (concentration of the solute).

[0014] Furthermore, the precipitant in step (1) is sodium carbonate or sodium hydroxide.

[0015] Furthermore, the concentration of the complexing agent solution in step (1) is 0.5-5 mol / L (solute concentration).

[0016] Furthermore, the complexing agent in step (1) is aqueous ammonia.

[0017] Furthermore, in the step (2), the volume flow ratio of the three solutions of nickel-cobalt-manganese metal ion solution, precipitant solution and complexing agent solution in the metering pump is 2:1:1.

[0018] Furthermore, the reaction temperature in step (2) is 40-65° C., the stirring speed is 500-900 r / min, the reaction pH is 7.5-11.5, and the reaction time is 30-80 h.

[0019] Furthermore, the D50 of the nickel-cobalt-manganese composite material precursor described in step (3) is ≤0.8 microns.

[0020] Furthermore, the lithium-rich manganese-based positive electrode precursor Mn x Ni y Co z (OH) 2or Mn x Ni y Co z CO 3 The molar ratio of phosphate, aluminum and titanium is (650-800):3:(0.2-0.5):(1.5-1.8).

[0021] Furthermore, the titanium source described in step (4) is one or more of tetraethyl titanate, tetrapropyl titanate, isopropyl titanate, tetrabutyl titanate or isobutyl titanate, titanium dioxide, titanium hydroxide, and titanium tetrachloride.

[0022] Furthermore, the aluminum source in step (4) is one or more of aluminum trichloride, aluminum sulfate or aluminum nitrate.

[0023] Furthermore, the phosphate source in step (4) is one or more of phosphoric acid, ammonium hydrogen phosphate, and diammonium dihydrogen phosphate.

[0024] Furthermore, the organic solvent described in step (4) is one or more of anhydrous ethanol, propanol, isopropanol, butanol, and isobutanol.

[0025] Furthermore, the molar ratio of the lithium source in step (5) to the aluminum-titanium phosphate-coated precursor is 1-1.6:1.

[0026] Furthermore, the sintering at 400-950° C. in step (5) is specifically: after mixing the aluminum-titanium phosphate-coated precursor with the lithium source, first sintering at 400-600° C. for 4-7 hours, and then sintering at 700-950° C. for 8-18 hours.

[0027] Furthermore, the sintering heating rate in step (5) is controlled at ≤15°C / min.

[0028] Furthermore, the lithium source in step (5) is one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxide or lithium acetate.

[0029] The present application also provides a fast ion conductor coated lithium-rich manganese-based positive electrode material obtained by the preparation method of the modified lithium-rich manganese-based positive electrode material described above. The structural formula of the positive electrode material is Li b Mn x Ni y Co z CO 3 @Li 1+a Al a Ti 2-a (PO 4 ) 3 ; where 0.5≤x<1, 0.1 <y<0.5,0.2≤a≤0.5,0.8<b<1.5。

[0030] Advantages and beneficial effects of this application:

[0031] 1. The present application proposes a coating method for lithium-rich manganese-based positive electrode materials, which is wet-coated by direct wet method of precursor and then mixed sintering. Compared with the existing coating scheme, the secondary sintering is omitted and the process steps are simplified. The existing common solid electrolyte coating is generally solid-phase direct mixing and secondary sintering. The general solid-phase mixing and low-temperature secondary sintering are difficult to achieve uniform coating and close adhesion between the substrate and the coating, and the rate and cycle improvement are limited; the substrate material of the present application includes a lithium-rich manganese-based positive electrode material and a fast ion conductor coated on the surface, and the fast ion conductor includes Li 1+a Al a Ti 2-a (PO 4 ) 3 ; Surface coating with fast ion conductors with high lithium ion conductivity has been proven to be a modification method that can simultaneously improve the rate performance and cycle performance of the positive electrode material. The coating of fast ion conductors avoids direct contact between the positive electrode material and the electrolyte, while inhibiting the side reactions between the positive electrode material and the electrolyte, effectively improving the lithium ion transmission capacity, and enhancing the discharge specific capacity and rate performance.

[0032] 2. The present application firstly wet-coats the precursor, and then adds a lithium source for mixed sintering, so as to realize the simultaneous generation of the coating layer and the inner layer, and realize a more uniform coating of the coating layer and the formation of a tighter chemical bond, so that the coating layer is not easy to fall off during the battery cycle, and can improve the rate performance and cycle performance of lithium-ion battery materials, and the method is simple and easy to implement, so it can realize industrialized scale-up production; it is conducive to the design and realization of high-safety, high-specific energy, and long-life lithium-ion batteries. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 The first charge and discharge curves of the lithium-rich manganese-based positive electrode material prepared in Example 1 and the uncoated lithium-rich manganese-based positive electrode material (2.0-4.6V, 0.1C conditions).

[0034] Figure 2 The first charge and discharge diagram of the lithium-rich manganese-based positive electrode material prepared in Example 1 and the uncoated lithium-rich manganese-based positive electrode material, as well as the second cycle of charge and discharge diagram in Example 1 (2.0-4.8V, 0.1C conditions).

[0035] Figure 3 The discharge specific capacity rate cycle diagram of the lithium-rich manganese-based positive electrode material prepared in Example 1 and the uncoated lithium-rich manganese-based positive electrode material (2.0-4.6V, 0.1C conditions).

[0036] Figure 4 This is the first electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 1.

[0037] Figure 5 This is the second electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 1.

[0038] Figure 6 This is the third electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 1.

[0039] Figure 7 This is the fourth electron microscope image of the lithium-rich manganese-based positive electrode material prepared in Example 1. DETAILED DESCRIPTION

[0040] In order to make the above-mentioned purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are described in detail below in combination with the examples. A method for preparing a lithium-rich manganese-based positive electrode material and the obtained positive electrode material. In the following description, many specific details are set forth to facilitate a full understanding of the present application. However, the present application can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present application. Therefore, the present application is not limited to the specific embodiments disclosed below.

[0041] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art to which this application belongs. The terms used herein in the specification of this application are only for the purpose of describing specific embodiments and are not intended to limit this application. The term "and / or" used herein includes any and all combinations of one or more of the related listed items.

[0042] In the following specific implementations of the present application, it should be noted that the raw materials involved in each step are selected from the following raw materials, and the raw materials are all commercially available products that can be obtained conventionally in the art unless otherwise specified:

[0043] The nickel-cobalt-manganese metal ion solution described in the present application can be prepared by mixing nickel sulfate, cobalt sulfate and manganese sulfate compounds or nickel nitrate, cobalt nitrate and manganese nitrate compounds with water; the precipitant solution is prepared by mixing sodium carbonate or sodium hydroxide with water, and the complexing agent solution is prepared by mixing ammonia water with water; the titanium source described in the present application is one or more of tetraethyl titanate, tetrapropyl titanate, isopropyl titanate, tetrabutyl titanate or isobutyl titanate, titanium dioxide, titanium hydroxide, and titanium tetrachloride; the aluminum source is one or more of aluminum trichloride, aluminum sulfate or aluminum nitrate; the phosphate source is one or more of phosphoric acid, ammonium hydrogen phosphate, and diammonium dihydrogen phosphate; the organic solvent is one or more of anhydrous ethanol, propanol, isopropanol, butanol, and isobutanol; the lithium source is one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxide or lithium acetate.

[0044] Example 1

[0045] A method for preparing a modified lithium-rich manganese-based positive electrode material comprises the following steps:

[0046] (1) preparing a 2 mol / L (total molar concentration of nickel, cobalt and manganese) mixed solution, i.e., a nickel-cobalt-manganese metal ion solution, by respectively mixing nickel sulfate, cobalt sulfate and manganese sulfate compounds in a molar ratio of 1:1:4; specifically, weighing nickel sulfate, cobalt sulfate and manganese sulfate compounds in the above molar ratio, and then mixing them with deionized water;

[0047] (2) preparing a 2 mol / L sodium carbonate solution as a precipitant (carbonate precursor) and a 0.8 mol / L ammonia solution as a complexing agent; specifically, mixing sodium carbonate with water to obtain a precipitant solution, and preparing the ammonia solution into a 0.8 mol / L aqueous solution;

[0048] (3) adding the mixed salt solution, precipitant and complexing agent (the volume flow ratio of the three in the metering pump is 2:1:1) into a coprecipitation reactor through a metering pump, controlling the temperature of the reactor to 55° C., the stirring speed to 750 r / min, the reaction pH to about 8.5, and performing the coprecipitation reaction for 40 hours to obtain a nickel-cobalt-manganese carbonate suspension;

[0049] (4) The suspension obtained in the above step (3) is washed (washed with water), filtered, and dried to obtain a Ni 0.167 Co 0.167 Mn 0.667 CO 3 A nickel-cobalt-manganese lithium-rich manganese-based carbonate precursor, with a precursor D50 of 0.7 microns;

[0050] (5) Disperse the above 2 kg of precursor in 1400 g of ethanol solution and heat to 60° C. with stirring to obtain a brown-yellow solution;

[0051] (6) adding 9.02 g of phosphoric acid (85 wt.%) and stirring evenly, and then adding 2.94 g of an aluminum source (aluminum nitrate nonahydrate) and 17.22 g of a titanium source (tetrabutyl titanate), stirring at 60° C. for 6 hours to obtain a brown-yellow suspension, wherein the molar ratio of aluminum, titanium and phosphate is 0.3:1.7:3;

[0052] (7) placing the brown-yellow mixed liquid in an oven at 80° C. for 12 h, removing the ethanol solvent, and grinding to obtain a composite A;

[0053] (8) The precursor in the composite A (i.e., 2 kg of the precursor described in step (5)) and lithium carbonate are mixed in a molar ratio of 1:1.41, and then the mixed materials are sintered at 500°C for 5 h and 850°C for 12 h. After the sintering is completed, the mixed materials are sieved to obtain a coated lithium-rich manganese-based positive electrode material Li 1.4 Ni 0.167 Co 0.167 Mn 0.667 O 2 @Li 1.3 Al 0.3 Ti 1.7 (PO 4 ) 3 ;

[0054] (9) The above-mentioned lithium-rich manganese-based positive electrode material was subjected to a buckle test, and a charge and discharge test was performed at 2.0-4.6V and 0.1C. After testing, the above-mentioned material 2.0-4.6V, the first cycle discharge capacity can reach 270mAh / g, the first coulombic efficiency of the material half-cell reaches 90%, the 200-cycle capacity retention rate is 90%, and the compaction is 2.9 (the compaction here is 2.9 compaction density).

[0055] Example 2

[0056] A method for preparing a modified lithium-rich manganese-based positive electrode material, characterized in that it comprises the following steps:

[0057] (1) nickel sulfate, cobalt sulfate and manganese sulfate compounds are prepared in a molar ratio of 35:5:60 to prepare a 2 mol / L (total molar concentration of nickel, cobalt and manganese) mixed solution, i.e., a nickel-cobalt-manganese metal ion solution, in a 50 L mixed solution; specifically, nickel sulfate, cobalt sulfate and manganese sulfate compounds are weighed in the above molar ratio, and then mixed with deionized water;

[0058] (2) preparing a 2 mol / L sodium carbonate solution as a precipitant and a 0.8 mol / L ammonia solution as a complexing agent; specifically, mixing sodium carbonate with water to obtain a precipitant solution, and preparing the ammonia solution into a 0.8 mol / L aqueous solution;

[0059] (3) adding the mixed salt solution, precipitant and complexing agent (the volume flow ratio of the three in the metering pump is 2:1:1) into a coprecipitation reactor through a metering pump, controlling the reactor temperature at 65° C., the stirring speed at 700 r / min, and the reaction pH at about 8.5, and performing the coprecipitation reaction for 35 hours to obtain a nickel-cobalt-manganese carbonate suspension;

[0060] (4) The above-mentioned material precursor suspension is washed, filtered and dried to obtain a Ni 0.35 Co 0.05 Mn0.65 CO 3 Composition: nickel-cobalt-manganese-rich lithium-manganese-based carbonate precursor; precursor D50 = 0.8 microns;

[0061] (5) Disperse the above 2 kg of precursor in 700 g of ethanol solution and heat to 60 ° C. Stir to obtain a brown-yellow solution.

[0062] (6) 9.02 g of phosphoric acid (85 wt.%) was added and stirred evenly, and then 1.95 g of an aluminum source (aluminum nitrate nonahydrate) and 18.23 g of a titanium source (tetrabutyl titanate) were added and stirred at 60° C. for 6 hours to obtain a brown-yellow suspension. The molar ratio of aluminum, titanium and phosphate was 0.2:1.8:3.

[0063] (7) placing the brown-yellow mixed liquid in an oven at 80° C. for 12 h, removing the ethanol solvent, and grinding to obtain a composite A;

[0064] (8) The precursor and lithium carbonate in the composite have a molar ratio of 1:1.31, and the mixed materials are sintered at 500°C for 5h and 800°C for 16h, and the coated lithium-rich manganese-based positive electrode material Li is obtained by sieving. 1.3 Ni 0.35 Co 0.05 Mn 0.60 O 2 @Li 1.2 Al 0.2 Ti 1.8 (PO 4 ) 3 ;

[0065] (9) The above-mentioned lithium-rich manganese-based positive electrode material was subjected to a charge-discharge test at 2.0-4.6V and 0.1C. After testing, the above-mentioned material 2.0-4.6V, the first cycle discharge capacity can reach 250mAh / g, the material half-cell first coulomb efficiency reaches 90%, and the 200-cycle capacity retention rate is 90%. The compaction is 2.8.

[0066] Example 3

[0067] A method for preparing a modified lithium-rich manganese-based positive electrode material, characterized in that it comprises the following steps:

[0068] (1) nickel sulfate, cobalt sulfate and manganese sulfate compounds are prepared in a molar ratio of 32:3:65 (total molar concentration of the three elements of nickel, cobalt and manganese) to prepare 50L of a mixed solution, i.e., a nickel-cobalt-manganese metal ion solution; specifically, nickel sulfate, cobalt sulfate and manganese sulfate compounds are weighed in the above molar ratio, and then mixed with deionized water;

[0069] (2) preparing a 10 mol / L precipitant sodium hydroxide solution as a precipitant (hydroxide precursor) and a 1 mol / L ammonia aqueous solution as a complexing agent; specifically, mixing sodium hydroxide with water to obtain a precipitant solution, and preparing the ammonia aqueous solution to a 1 mol / L aqueous solution;

[0070] (3) adding the mixed salt solution, precipitant and complexing agent (the volume flow ratio of the three in the metering pump is 2:1:1) into the coprecipitation reactor through the metering pump, controlling the reactor temperature at 55° C., the stirring speed at 600 r / min, the reaction pH at about 11, and performing the coprecipitation reaction for 70 hours to obtain a nickel-cobalt-manganese hydroxide precursor suspension;

[0071] (4) The above-mentioned material precursor suspension is washed, filtered and dried to obtain a Ni 0.32 Co 0.03 Mn 0.65 (OH) 2 Composition: nickel-cobalt-manganese-rich lithium-manganese-based hydroxide precursor, precursor D50 = 0.8 micron;

[0072] (5) Disperse 2 kg of the above precursor in 1400 g of ethanol solution, heat to 60° C., and stir to obtain a black solution;

[0073] (6) Then, 9.02 g of phosphoric acid (85 wt.%) was added to the black solution of step (5) and the mixture was stirred evenly. Then, 3.92 g of an aluminum source (aluminum nitrate nonahydrate) and 18.40 g of a titanium source (tetrabutyl titanate) were added and stirred at 60° C. for 6 hours to obtain a black suspension. The molar ratio of aluminum, titanium and phosphate was 0.4:1.6:3.

[0074] (7) placing the black suspension mixture in an oven at 80° C. for 12 h to remove the ethanol solvent, and then grinding to obtain a composite A;

[0075] (8) The precursor and lithium carbonate in the composite A have a molar ratio of 1:1.46, and the mixed materials are sintered at 500°C for 5h and 900°C for 14h, and the coated lithium-rich manganese-based positive electrode material Li 1.45 Ni 0.32 Co 0.03 Mn 0.65 O 2 @Li 1.4 Al 0.4 Ti 1.6 (PO4) 3 ;

[0076] (9) The above-mentioned lithium-rich manganese-based positive electrode material was subjected to a charge-discharge test at 2.0-4.6V and 0.1C. After testing, the above-mentioned material 2.0-4.6V, the first cycle discharge capacity can reach 230mAh / g, the first coulomb efficiency of the material half-cell reaches 85%, and the 200-cycle capacity retention rate is 90%. Although the capacity of this material is lower than that of the carbonate-based lithium-rich manganese-based positive electrode material, the compaction is relatively high, with a compaction of 3.1.

[0077] Example 4

[0078] A method for preparing a modified lithium-rich manganese-based positive electrode material, characterized in that it comprises the following steps:

[0079] (1) nickel sulfate, cobalt sulfate and manganese sulfate compounds are prepared in a molar ratio of 29:0.8:63 to prepare a 2 mol / L (total molar concentration of nickel, cobalt and manganese) mixed solution, i.e., a nickel-cobalt-manganese metal ion solution, in 50 L; specifically, nickel sulfate, cobalt sulfate and manganese sulfate compounds are weighed in the above molar ratio, and then mixed with deionized water;

[0080] (2) preparing a 10 mol / L precipitant sodium hydroxide solution as a precipitant (sodium hydroxide precursor) and a 1 mol / L ammonia aqueous solution as a complexing agent; specifically, mixing sodium hydroxide with water to obtain a precipitant solution, and preparing the ammonia aqueous solution to be a 1 mol / L aqueous solution;

[0081] (3) adding the mixed salt solution, precipitant and complexing agent (the volume flow ratio of the three in the metering pump is 2:1:1) into a coprecipitation reactor through a metering pump, controlling the reactor temperature at 55° C., stirring speed at 600 r / min, and reaction pH at about 11, and performing the coprecipitation reaction for 65 hours to obtain a nickel-cobalt-manganese hydroxide precursor suspension;

[0082] (4) The above-mentioned material precursor suspension is washed, filtered and dried to obtain a Ni 0.29 Co 0.08 Mn 0.63 (OH) 2 Composition: nickel-cobalt-manganese-rich lithium-manganese-based hydroxide precursor, precursor D50 = 0.7 micron;

[0083] (5) Disperse 2 kg of the above precursor in 1400 g of ethanol solution, heat to 60° C., and stir to obtain a black solution;

[0084] (6) Then, 9.02 g of phosphoric acid (85 wt.%) was added to the black solution of step (5) and stirred evenly, and then 4.72 g of an aluminum source (aluminum sulfate) and 4.06 g of a titanium source (titanium dioxide) were added and stirred at 60° C. for 6 hours to obtain a black suspension, wherein the molar ratio of the aluminum, titanium and phosphate mentioned above was 0.3:1.7:3;

[0085] (7) placing the black mixed liquid in an oven at 80° C. for 12 h, removing the ethanol solvent, and grinding to obtain a composite A;

[0086] (8) The molar ratio of the precursor and lithium hydroxide in the composite A is 1:1.36, and the mixed materials are sintered. The sintering process is 500°C for 5h and 760°C for 12h, and the coated lithium-rich manganese-based positive electrode material Li 1.35 Ni 0.29 Co 0.08 Mn 0.63 O 2 @Li 1.3 Al 0.3 Ti 1.7 (PO4) 3 ;

[0087] (9) The above-mentioned lithium-rich manganese-based positive electrode material was subjected to a charge-discharge test at 2.0-4.6V and 0.1C. After testing, the above-mentioned material 2.0-4.6V, the first cycle discharge capacity can reach 260mAh / g, the material half-cell first coulomb efficiency reaches 90%, and the 200-cycle capacity retention rate is 90%. The compaction is 2.6.

[0088] The product prepared in Example 1 of the present application was tested. Figure 1 The first charge and discharge curves of the lithium-rich manganese-based positive electrode material and the uncoated lithium-rich manganese-based positive electrode material prepared in Example 1 (2.0-4.6V, 0.1C condition), where the black curve is the uncoated material (without Li 1+a Al a Ti 2-a (PO4) 3 ) of the charge-discharge voltage and specific capacity curve, the red one is coated in the present embodiment 1, and it can be seen that the discharge specific capacity of the material coated with the red curve will increase by 10mah / g; Figure 2 The first charge and discharge of the lithium-rich manganese-based positive electrode material prepared in Example 1 and the uncoated lithium-rich manganese-based positive electrode material and the second cycle charge and discharge curve diagram in Example 1 (2.0-4.8V, 0.1C condition), where black is uncoated, red is the coated material in Example 1, and blue is the second cycle charge and discharge ratio curve of the coated material. Since the performance of the first cycle was not fully utilized, the discharge specific capacity improvement of the coating was reflected in the second cycle, and the charging condition was 2.0-4.8V; Figure 3 The discharge specific capacity rate cycle diagram (2.0-4.6V, 0.1C condition) of the lithium-rich manganese-based positive electrode material prepared in Example 1 and the uncoated lithium-rich manganese-based positive electrode material, wherein the blue is the uncoated rate cycle diagram, and the red is the coated rate cycle diagram in Example 1. It can be seen from the figure that the rate performance of the coated one is better than that of the uncoated one. From the perspective of rate performance, this diagram is indeed effective.

[0089] As attached Figure 4-7 The electron microscope images of the lithium-rich manganese-based positive electrode material prepared in the example are shown. From these electron microscope images, it can be seen that the lithium-rich manganese-based positive electrode material prepared in the present application has an ideal spherical complete structure and can show a clear microstructure at different magnifications.

[0090] Through the above embodiments and test results, it can be seen that the technical solution of the present application first wet-coats the precursor, and then adds a lithium source for mixed sintering, so as to realize the simultaneous generation of the coating layer and the inner layer, and realize a more uniform coating of the coating layer and a tighter chemical bond, so that the coating layer is not easy to fall off during the battery cycle, which can improve the rate performance and cycle performance of lithium-ion battery materials, and the method is simple and easy to implement, so it can be industrialized and scaled up; it is conducive to the design and realization of high-safety, high-specific energy, and long-life lithium-ion batteries; in addition, the coating layer of the present application adopts a fast ion conductor Li 1+ a Al a Ti 2-a (PO 4 ) 3 It can be seen from the test results of this application that surface coating with a fast ion conductor with high lithium ion conductivity can simultaneously improve the rate performance and cycle performance of the positive electrode material. The coating of the fast ion conductor avoids direct contact between the positive electrode material and the electrolyte, and while inhibiting the side reaction between the positive electrode material and the electrolyte, it effectively improves the lithium ion transmission capacity, thereby improving the discharge specific capacity and rate performance.

Claims

1. A method for preparing a modified lithium-rich manganese-based positive electrode material, characterized in that: The steps of the method include: (1) First, prepare a nickel-cobalt-manganese metal ion solution, a precipitant solution, and a complexing agent solution, respectively, wherein the nickel-cobalt-manganese metal ion solution, the precipitant solution, and the complexing agent solution are all aqueous solutions; (2) adding a nickel, cobalt and manganese metal ion solution, a precipitant solution and a complexing agent solution into a reaction kettle through a metering pump to react and obtain a suspension; (3) washing, filtering and drying the suspension to obtain a nickel-cobalt-manganese composite material precursor; the chemical formula of the nickel-cobalt-manganese composite material precursor is Mn x Ni y Co z (OH)2 or Mn x Ni y Co z CO3, where 0.5≤x<1, 0.1 <y<0.5,0<z<0.3; (4) The nickel-cobalt-manganese composite material precursor Mn x Ni y Co z (OH)2 or Mn x Ni y Co z CO3, titanium source, aluminum source, and phosphate source are added to an organic solvent and mixed, heated and stirred at 40-80°C, and then dried at 80-120°C to obtain an aluminum-titanium phosphate-coated precursor; (5) The aluminum-titanium phosphate-coated precursor is ground and mixed with a lithium source, and sintered at 400-950° C. to obtain a fast ion conductor-coated lithium-rich manganese-based positive electrode material.

2. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The concentration of the nickel-cobalt-manganese metal ion solution described in step (1) is 0.5-3moL / L, and the molar ratio of nickel salt, cobalt salt and manganese salt in the nickel-cobalt-manganese metal ion solution is (1-35):(0.8-5):(4-65); the concentration of the precipitant solution is 1-3moL / L; and the concentration of the complexing agent solution is 0.5-5moL / L.

3. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 2, characterized in that: The volume flow ratio of the three solutions of nickel-cobalt-manganese metal ion solution, precipitant solution and complexing agent solution in step (2) in the metering pump is 2:1:

1.

4. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 3, characterized in that: The reaction temperature in step (2) is 40-65° C., the stirring speed is 500-900 r / min, the reaction pH is 7.5-11.5, and the reaction time is 30-80 h; the D50 of the nickel-cobalt-manganese composite material precursor in step (3) is ≤0.8 μm.

5. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The lithium-rich manganese-based positive electrode precursor Mn described in step (4) x Ni y Co z (OH)2 or Mn x Ni y Co z The molar ratio of CO3, phosphate, aluminum and titanium is (650-800):3:(0.2-0.5):(1.5-1.8).

6. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 5, characterized in that: The titanium source described in step (4) is one or more of tetraethyl titanate, tetrapropyl titanate, isopropyl titanate, tetrabutyl titanate or isobutyl titanate, titanium dioxide, titanium hydroxide, and titanium tetrachloride; The aluminum source in step (4) is one or more of aluminum trichloride, aluminum sulfate or aluminum nitrate; The phosphate source in step (4) is one or more of phosphoric acid, ammonium hydrogen phosphate, and diammonium dihydrogen phosphate; The organic solvent described in step (4) is one or more of anhydrous ethanol, propanol, isopropanol, butanol, and isobutanol.

7. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 1, characterized in that: The molar ratio of the lithium source described in step (5) to the aluminum-titanium phosphate-coated precursor is 1-1.6:

1.

8. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 7, characterized in that: The sintering at 400-950°C described in step (5) is specifically: after mixing the aluminum-titanium phosphate-coated precursor with the lithium source, first sintering at 400-600°C for 4-7h, and then sintering at 700-950°C for 8-18h; the sintering heating rate described in step (5) is controlled at ≤15°C / min.

9. The method for preparing the modified lithium-rich manganese-based positive electrode material according to claim 8, characterized in that: The lithium source is one or more of lithium hydroxide, lithium carbonate, lithium nitrate, lithium oxide or lithium acetate.

10. A modified lithium-rich manganese-based positive electrode material, characterized in that: The fast ion conductor-coated lithium-rich manganese-based positive electrode material prepared by any one of claims 1 to 9 has a structural formula of Li b Mn x Ni y Co z O 2@ Li 1+a Al a Ti 2-a (PO4)3, where 0.5≤x<1, 0.1 <y<0.5,z=1-x-y,0.2≤a≤0.5,0.8<b<1.5。